2021
DOI: 10.3390/ijerph18052230
|View full text |Cite
|
Sign up to set email alerts
|

Hospitalization Costs of Lower Limb Ulcerations and Amputations in Patients with Diabetes in Romania

Abstract: In this retrospective case-control study conducted in Cluj-Napoca, Romania, we assessed the effect of ulcerations/amputations on hospitalization costs of patients with diabetes. Patients with (Group 1) or without (Group 2) ulcerations/amputations (case-control ratio 3:1) admitted to a single diabetes center between 2012–2017 were included. The effects of hospitalization days, age, duration of diabetes, body mass index and glycated hemoglobin (HbA1c) on total costs was explored using a multivariate linear regre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
1
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 27 publications
1
1
0
1
Order By: Relevance
“…If the influence of the nature of the hospital on the hospitalization cost for diabetic patients was ignored, and only the influence of the diabetes patient’s situation on the hospitalization cost was considered, then the hospitalization cost of diabetic patients in a Chinese medicine hospital was mainly related to the length of stay, the type of diabetes, and the complications associated with comorbidities. In this case, the number of days in hospital was the strongest factor affecting hospitalization cost, which was consistent with the findings of Sima, D.I., Bala, C. et al [ 23 , 24 ].…”
Section: Discussionsupporting
confidence: 92%
“…If the influence of the nature of the hospital on the hospitalization cost for diabetic patients was ignored, and only the influence of the diabetes patient’s situation on the hospitalization cost was considered, then the hospitalization cost of diabetic patients in a Chinese medicine hospital was mainly related to the length of stay, the type of diabetes, and the complications associated with comorbidities. In this case, the number of days in hospital was the strongest factor affecting hospitalization cost, which was consistent with the findings of Sima, D.I., Bala, C. et al [ 23 , 24 ].…”
Section: Discussionsupporting
confidence: 92%
“…An analysis of the outpatient diabetes costs in Romania from 2000 to 2017 reported that diabetes accounted for 21.3% of the total funds allocated for national healthcare programs, with an average growth rate of 25.4% during this period [ 6 ]. When assessing the hospitalization costs of treating complications of diabetes in Romanian patients, only one recent study is available, which reported that the cost was 40% higher in patients presenting with lower limb ulcerations and amputations compared to those not presenting with this complication [ 7 ]. Even at additional costs, optimal treatment of people with diabetes is the main solution for preventing acute and chronic complications, which would result in an even higher financial burden.…”
Section: Introductionmentioning
confidence: 99%
“…The economic burden of hospitalization costs for patients with DFUs was previously reported [101,102]. The costs reported in Romania for DFU hospitalization were found to be 40% higher when compared to those without DFUs [103], still not so high as the costs reported in most of the European countries [104]. To our knowledge, there is no previously published paper analyzing the costs for DFUs outside hospitalization in Romania.…”
Section: Factors That Influenced Buying Behaviormentioning
confidence: 97%
“…To our knowledge, there is no previously published paper analyzing the costs for DFUs outside hospitalization in Romania. Also, the previously analyzed costs of hospitalized DFUs did not include off-loading treatment, postulating that under treatment or lack of appropriate therapies for DFUs in patients with DM are missing as standard care in Romania [103].…”
Section: Factors That Influenced Buying Behaviormentioning
confidence: 99%